2017
DOI: 10.1177/0031512517730414
|View full text |Cite
|
Sign up to set email alerts
|

What Physical Fitness Component Is Most Closely Associated With Adolescents' Blood Pressure?

Abstract: This study aimed to determine which of four selected physical fitness variables, would be most associated with blood pressure changes (systolic and diastolic) in a large sample of adolescents. This was a descriptive and cross-sectional, epidemiological study of 1,117 adolescents aged 14-19 years from southern Brazil. Systolic and diastolic blood pressure were measured by a digital pressure device, and the selected physical fitness variables were body composition (body mass index), flexibility (sit-and-reach te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
3
7
1
Order By: Relevance
“…Regarding the location of these studies, it was identified that the Southern and Southeastern regions of Brazil were those that most published articles on MS in children and adolescents, with 18 studies 7-9,12-27 . Regarding the design of included studies, 22 had cross-sectional 3,7-9,14-21, [23][24][25][27][28][29][30][31][32][33][34][35] and five longitudinal design 12,13,22,26,36 (Table 1). The studies covered different primary goals as can be observed in Table 1; however, all of them performed MS measurements as defined in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the location of these studies, it was identified that the Southern and Southeastern regions of Brazil were those that most published articles on MS in children and adolescents, with 18 studies 7-9,12-27 . Regarding the design of included studies, 22 had cross-sectional 3,7-9,14-21, [23][24][25][27][28][29][30][31][32][33][34][35] and five longitudinal design 12,13,22,26,36 (Table 1). The studies covered different primary goals as can be observed in Table 1; however, all of them performed MS measurements as defined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Freitas et al, 35 Montes Claros, MG No study was classified with low methodological quality / high risk of bias. Moderate methodological quality/moderate risk of bias was verified in ten studies (37.0%) 7,12,13,15,19,21,23,26,28,29 , while seventeen studies … continue (67.0%) 3,8,9,14,16,17,20,22,24,25,27,[30][31][32][33]35,36 were classified with high methodological quality / low risk of bias (Table 2). MS was investigated in fourteen different ways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence from both observational and prospective studies in high-and middle-income societies has shown overweight youth with low leg muscle power exhibit unfavorable cardiometabolic disease risk, including high BP [20,21]. Although HTN, like in the developed world is becoming a health problem in sub-Saharan Africa, the significance of fatness and leg muscle power in the development of HTN remains to be fully investigated among Nigerian youth.…”
Section: Discussionmentioning
confidence: 99%